Social Media Utilization by the Ministry of Tourism and Creative Economy in Building Tourism Image in the Digital Communication Era (Case Study: Instagram Account @Pesona.Indonesia) - Sihombing, Tobias; Nirmalawati, Federika; Wianastiti, Devania Aisya; Nur Aini, Saqia Aulia; Iswanti, Salsabila Cahya (UMSU, 2025)
This study explores the utilization of the Instagram account @pesona.indonesia by the Ministry of Tourism and Creative Economy (Kemenparekraf) in building Indonesia’s tourism image in the digital communication era. Employing a descriptive qualitative approach, the research analyzes visual content, narratives, and user interactions over the past three months. The findings reveal that the account effectively applies new media principles such as digitalization, interactivity, and democratization. The content strategy goes beyond merely delivering information; it creates compelling visual experiences, reinforces cultural identity, and fosters audience engagement. High levels of user participation through comments, likes, and content sharing indicate successful two-way communication that shapes a positive perception of Indonesia as a tourism destination. These findings emphasize the strategic role of social media in tourism promotion and cultural diplomacy within the digital sphere.